How to Encourage Social Entrepreneurship Action? Using Web 2.0 Technologies in Higher Education Institutions - García-Morales, Víctor Jesus; Martín-Rojas, Rodrigo; Garde-Sánchez, Raquel (Journal of Business Ethics, 2020)
University students will be our future business leaders, and will have to address social problems caused by business by implementing solutions such as social entrepreneurship ventures. In order to facilitate the learning process that will foster social entrepreneurship, however, a more holistic pedagogy is needed. Based on learning theory, we propose that students' social entrepreneurship actions will depend on their learning about CSR and their absorptive capacity. We propose that instructors and higher education institutions can enhance this absorptive capacity by exploiting Web 2.0 technologies. We tested our proposition with a sample of 425 university students using structural equation modeling and found support for the proposed relationships.
Keywords: Entrepreneuriat; Internet; Libre accès; Soutien; social